(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2024)
This article illustrates that a scientific research is carried out about the importance of teaching the language of the media language as a subject to students , and general research results about its importance , relevance to the professional direction , its purpose , the importance of using methods during the teaching , as well as, general summaries and results are given.